Screening of Ultraviolet-Induced Thermotolerant Yeast Mutants and Their Performance - Xiaodi Li; Yan Lin; Hainan Kong; Zhiquan Wang (Fermentation, 2023)
The simultaneous saccharification and fermentation (SSF) technique holds promise for the conversion of lignocellulose to ethanol. However, the optimal fermentation temperature of yeast is lower than the enzymatic hydrolysis temperature of the saccharification process, which leads to the temperature of the actual production process of SSF usually being lower than 38 °C. In this work, two ultraviolet (UV)-induced mutations were performed step by step using Saccharomyces cerevisiae BY4742 as the original strain to enable the yeast to perform well at higher temperatures. Thermotolerant strains obtained through mutagenesis and screening, YUV1-1 and YUV2-2, were utilized for fermentation and SSF at a targeted temperature of 40 °C. They obtained ethanol yields comparable to those at 38 °C in SSF, whereas the ethanol yields of the original strain at 40 °C decreased by about 10% compared to those at 38 °C. This study proves that thermotolerant strains adapted to elevated fermentation and SSF temperatures can be obtained through UV mutagenesis and screening, thereby increasing the stability of the fermentation and SSF processes and lowering the subsequent distillation costs.